The Role of Organizational Culture and Technology in Shaping Digital Brand Trust - Tawil, Yulizar Pramudika; Ananda, Annisa Rizki; Fatmawati, Yuli; Bernardianto, Raden Biroum (Sinergi International Journal of Communication Sciences, 2024)
This study explores the integration of interactive CSR communication, employee advocacy, and digital co-creation as strategic tools in managing brand reputation in the digital era. With increasing digital engagement from younger consumers and heightened brand vulnerability on social media, this research aims to understand how interactive communication practices can enhance brand trust and mitigate reputational crises. The study adopts a narrative review methodology, synthesizing recent literature on AI-enabled communication tools, sentiment analysis, employee-driven advocacy, and digital storytelling in crisis communication and CSR campaigns. The findings reveal that explicit and participatory CSR communication, supported by real-time feedback mechanisms and AI technologies, significantly strengthens brand authenticity and stakeholder trust. Moreover, organizational readiness in terms of culture, regulation, and technological infrastructure is found to be a key enabler in sustaining message coherence and credibility. Employee advocacy further amplifies brand identity when internal communication aligns with external narratives. The study emphasizes the need for holistic communication strategies that combine technological innovation with ethical oversight and stakeholder inclusion. As digital transformation reshapes corporate communication, proactive integration of sentiment analytics, influencer engagement, and cross-functional collaboration is essential. The insights provided here offer practical and theoretical guidance for designing resilient communication systems and call for future research into digital trust, narrative dynamics, and cross-cultural communication impacts.